PEMANFAATAN MEDIA DALAM PEMBELAJARAN TARI DI TAMAN KANAK-KANAK (Harmonia: Journal of Arts Research and Education, 2010)
Learning the art, especially the art of dancing in the kindergarten (TK), until recently, is generally done conventionally. Teachers give examples of motions then were followed by the students, and later accompanied with music. Such activity is repeated. Learning to dance, as a matter of fact, when packaged with media, besides has optimum result; fun learning can also be obtained. Less attractive of media packaging is indicated by the various educational background of the teachers. There are only a few who really possess kindergarten educational fields. Consequently, those who have just started teaching own very little special provision relating to learning in kindergarten. It is not surprising that there are deficiencies and limitations of knowledge, skills, and creativity of teachers in utilizing the media as a means of learning in kindergarten, more specifically learning dance.Kata kunci :Â Â  pemanfaatan, media, pembelajaran , taman kanak- kanak.